Influence of capsaicin infusion on secondary peristalsis in patients with gastroesophageal reflux disease - Yi, Chih-Hsun (World J Gastroenterol, 2016)
AIM: To determine whether capsaicin infusion could influence heartburn perception and secondary peristalsis in patients with gastroesophageal reflux disease (GERD). METHODS: Secondary peristalsis was performed with slow and rapid mid-esophageal injections of air in 10 patients with GERD. In a first protocol, saline and capsaicin-containing red pepper sauce infusions were randomly performed, whereas 2 consecutive sessions of capsaicin-containing red pepper sauce infusions were performed in a second protocol. Tested solutions including 5 mL of red pepper sauce diluted with 15 mL of saline and 20 mL of 0.9% saline were infused into the mid-esophagus via the manometric catheter at a rate of 10 mL/min with a randomized and double-blind fashion. During each study protocol, perception of heartburn, threshold volumes and peristaltic parameters for secondary peristalsis were analyzed and compared between different stimuli. RESULTS: Infusion of capsaicin significantly increased heartburn perception in patients with GERD (P < 0.001), whereas repeated capsaicin infusion significantly reduced heartburn perception (P = 0.003). Acute capsaicin infusion decreased threshold volume of secondary peristalsis (P = 0.001) and increased its frequency (P = 0.01) during rapid air injection. The prevalence of GERD patients with successive secondary peristalsis during slow air injection significantly increased after capsaicin infusion (P = 0.001). Repeated capsaicin infusion increased threshold volume of secondary peristalsis (P = 0.002) and reduced the frequency of secondary peristalsis (P = 0.02) during rapid air injection. CONCLUSION: Acute esophageal exposure to capsaicin enhances heartburn sensation and promotes secondary peristalsis in gastroesophageal reflux disease, but repetitive capsaicin infusion reverses these effects.